The Death of the Security Industry. - Schneier, B. (IEEE Security and privacy : building confidence in a networked world)
The entire IT security industry is an accident: an artifact of how the computer industry developed. Computers are hard to use, and you need an IT department staffed with experts to make it work. IT security is critical, but there's no earthly reason why users need to know what an intrusion detection system with stateful protocol analysis is, or why it's helpful in spotting SQL injection attacks. As IT fades into the background and becomes just another utility, users will simply expect it to work. The details of how it works won't matter.